134 Mutations in the sarcomere protein gene MYH7 in Ebstein's anomaly. (9th June 2011) - Rahman, T; Goodship, J; Postma, A; Engelen, K; Mulder, B; Klaassen, S; Keavney, B
Abstract : Background: Ebstein's anomaly is a rare congenital heart malformation characterised by adherence of the septal and posterior leaflets of the tricuspid valve to the underlying myocardium. As there have been reports of abnormal left ventricular morphology and function in patients with Ebstein's anomaly we hypothesised that mutations in the β-myosin heavy chain (MYH7) may be associated with Ebstein's anomaly. Methods: MYH7 mutation analysis was undertaken in 141 unrelated affected individuals with Ebstein's anomaly using next-generation sequencing on the 454 platform. 64 probands had no associated cardiac anomalies. The most common associated cardiac malformation were atrial septal defect (48 probands) and left ventricular non-compaction (LVNC) (7 probands). Where mutations were discovered, family studies were undertaken and the segregation of the mutation with disease was investigated. Results: Heterozygous mutations were identified in eight of the probands including six of the seven with LVNC. Two patients had the same mutation; of the seven distinct mutations, five were novel (four missense changes and an in-frame deletion) and two have been previously reported in patients with hypertrophic cardiomyopathy. Family studies revealed additional members with LVNC for three of the probands, one of whom also had a relative with Ebstein's anomaly. In these three pedigrees the mutation segregated with disease. Conclusions: Mutations in MYH7 occur relatively frequently in Ebstein's anomaly accompanied by LVNC. This study is another example of mutations in a sarcomere protein causing congenital heart malformation.